Comparison of the muscle-tendon complex behavior in the gastrocnemius during 4 types of human vertical jumping in vivo - Fukashiro, S. (International Journal of Sport & Health Science, 2006)
Behavior of fascicles and tendinous structures of the m. gastrocnemius medialis (MG) was quantitatively re-evaluated from the viewpoints of force-length and force-velocity relations during 4 types of human vertical jumping in vivo, based on our previous studies. Eight male subjects performed maximal-effort 1: ankle plantarflexion jumping (AJ) from the standing position, 2: squat jumping (SQJ) from the squat position, 3: counter movement jumping (CMJ) from the standing position, and 4: straight legged drop jumping (DJ) from a height of 0.20 m. Kinematic and kinetic data were obtained using a high-speed camera and a force platform system. Also, behavior of fascicles and tendinous structures were determined using ultrasonography. Vertical displacements of the body center of gravity from the standing position were 0.16m, 0.43m, 0.44m and 0.33m in AJ, SQJ, CMJ and DJ, respectively. During the take-off phase, there was no stretching of the fascicles of the MG in all jumping conditions. In AJ and SQJ, on the other hand, the fascicles of the MG shortened in the early take-off phase. As a result, 2.2J, 4.9J, 6.6J and 7.6J of elastic energy were stored in the tendinous structures of the MG in AJ, SQJ, CMJ and DJ, respectively. During the push-off phase, 2.1J (47% of total muscle-tendon complex work in the push-off phase), 4.4J (86%), 3.8J (79%) and 5.8J (75%) of the stored energy was reutilized in each of the conditions, respectively. The fascicles of the MG operated within the optimal range of the sarcomere force-length relationship during jumping. Also, the fascicles worked in the relatively low shortening velocity region of the instantaneous force-velocity relationship in all jumping conditions.